EFEKTIVITAS MODEL PROBLEM SOLVING DENGAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKATKAN KEMAMPUAN BERPIKIR KRITIS DAN MOTIVASI BELAJAR GEOGRAFI - Munasyaroh, Ulfi; Wijayanto, Pradika Adi; Sriyanto, Sriyanto; Benardi, Andi Irwan (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Critical thinking skills are essential for students not only to understand the material but also to solve everyday problems based on their knowledge. These critical thinking skills can be further developed when teachers create a learning environment that supports students in honing their critical thinking abilities, especially in learning geography. Student self-motivation is also a crucial aspect of successful learning. The integration of digitalization in education should be maximally utilized to enhance students' motivation and interest in learning geography. Augmented reality (AR) is one of the alternative digital technologies that can be used as a learning media. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group model. Data collection techniques included observation to assess the geography learning conditions at the research site, tests to measure students' critical thinking skills, questionnaires to determine students' motivation levels, and documentation. Data analysis techniques used were normality test, homogeneity test, N-Gain test, and descriptive percentage analysis. The results indicated that the model and media used were less effective in improving critical thinking skills, as evidenced by a low average N-Gain score of 0.0392 in the experimental class. Meanwhile, student learning motivation increased slightly by 0.33%, from 72.74% to 73.07%, which is categorized as high motivation.